The "first Deborah" - Genesis 35:8 in the literary and theological context - Olojede, F. (Faculty of Theology, University of the Free State, 2016)
Exegetes consider Genesis 35:8 an intrusive verse in the narrative of Genesis 35:1-15 because of its isolated mention of the death and burial of Deborah, Rebekah’s nurse. However, the analysis of the verse in its literary and theological context in this article shows that it has been strategically placed in the narrative to underscore, among other things, the important role of Deborah in the Bethel tradition and the Jacob Cycle, as well as the subtle pointer to the fact that little people also have a place in the overall narrative of God’s people.
Keywords: Deborah; Genesis 35:8; Wet nurse